Influence of biochar addition on gas permeability in unsaturated soil. Issue 1 (7th February 2019) - Garg, Ankit; Bordoloi, Sanandam; Ni, Junjun; Cai, Weiling; Maddibiona, Phani Gopal; Mei, Guoxiong; Poulsen, Tjalfe G.; Lin, Peng
Abstract : Biochar has been proposed as an alternative soil amendment in landfill cover. Its effects on soil hydraulic properties (e.g., soil water retention) have been explored to some extent, while its influence on landfill gas flow characteristics is not clear yet. The objective of this study is to investigate the water retention and gas permeability (kg ) of biochar-amended soil and its relationship with soil water content in unsaturated state. In total, three biochar contents (0, 5% and 10%) were considered in clay-sand mixtures. Soil suction, water content and gas pressure were measured continuously using a new in-house developed apparatus. Test results show that the presence of biochar increased soil water content and the increased amount was almost the same over a wide range of suction values (up to 3 MPa). kg increased linearly with soil suction in semi-log scale, regardless of the biochar content. 5% and 10% of biochar addition could decrease kg by up to 50% and 65% respectively, compared with that of the bare soil. kg decreased with water content for both soil and biochar amended soils. Moreover, the decrease rate of kg with water content became smaller when the biochar percentage was higher.